Autosomal Recessive Polycystic Kidney Disease—The Clinical Aspects and Diagnostic Challenges - Wicher, Dorota; Obrycki, Łukasz; Jankowska, Irena (Journal of Pediatric Genetics, 2020)
Autosomal recessive polycystic kidney disease (ARPKD) is one of the most common ciliopathies with kidney (nephromegaly, hypertension, renal dysfunction) and liver involvement (congenital hepatic fibrosis, dilated bile ducts). Clinical features also include growth failure and neurocognitive impairment. Plurality of clinical aspects requires multidisciplinary approach to treatment and care of patients. Until recently, diagnosis was based on clinical criteria. Results of genetic testing show the molecular basis of polycystic kidneys disease is heterogeneous, and differential diagnosis is essential. The aim of the article is to discuss the role of genetic testing and its difficulties in diagnostics of ARPKD in children.
Keywords: autosomal recessive polycystic kidney disease; congenital hepatic fibrosis; next-generation sequencing